The Relevance of the Application of Tat Twam Asi Local Wisdom in Managing Human Resources at Untag Banyuwangi - Ni Made Nadia Suta Pradhani; Ni Kadek Yuliandari (UNEJ e-Proceeding, 2021)
Management of Human Resources (HR) is an important thing that must be done by all companies or organizations. Human resources who have a strong character of local wisdom and are well managed by the company will certainly become qualified human resources. The quality of human resources can be assessed from many aspects, one of which is by looking at their attitudes and behavior at work. This research was conducted to look deeper into the relevance of the application of local wisdom Tat Twam Asi in managing human resources at Untag Banyuwangi. This study uses a qualitative descriptive analysis with in-depth interviews and direct observation. The results obtained are the concept of local wisdom Tat Twam Asi has been unconsciously implemented into the work concept by the informants. The implementation of Tat Twam Asi's local wisdom is reflected in attitudes such as mutual respect, mutual respect, mutual assistance, and other wise attitudes. Tat Twam Asi's local wisdom can be used as a guide in working, but it must be packaged in a more universal language so that it is easier to understand by all parties in University of Augst 1945 Banyuwangi. Keywords: Human Resources Management, Local Wisdom, Tat Twam Asi, Untag Banyuwangi.